Political Connections as Moderating Factors Affecting Tax Aggressiveness in Indonesian Mining Firms - Nazwa Anggita Az-Zahra; Fahmaninda Listiyani (Journal of Accounting Science, 2026)
General Background: Tax aggression remains a significant issue in developing countries as it can reduce government revenue and affect fiscal sustainability. Specific Background: In Indonesia, mining companies are considered vulnerable to aggressive tax practices due to their high capital requirements, complex financing structures, and close ties to government policy and regulation. Knowledge Gap: Previous studies on tax aggressiveness have yielded inconsistent findings, whilst evidence regarding the moderating role of political connections remains limited, particularly in the post-pandemic period. Objective: This study investigates the impact of firm characteristics on tax aggressiveness and the moderating function of political connections. Method: This study utilises secondary data from 29 mining companies listed on the Indonesia Stock Exchange over the period 2021–2024. The analysis was conducted using Moderated Regression Analysis (MRA). Results: The findings indicate that leverage has a significant positive effect on tax aggressiveness, whilst institutional ownership is significantly associated with lower tax aggressiveness. Political connections significantly moderate the relationship between institutional ownership and tax aggressiveness, thereby strengthening the link between institutional ownership and tax aggressiveness. Novelty: This study provides evidence regarding the role of political connections in shaping corporate tax behaviour in Indonesia’s post-pandemic mining sector. Implications: These findings highlight the importance of strengthening regulatory oversight and corporate transparency to curb tax aggression practices.